ANALISIS PENGARUH ASSET, PROFIT MARGIN, RASIO SOLVABILITAS DAN LIKUIDITAS TERHADAP KINERJA KEUANGAN ASURANSI (Studi Kasus Pada Perusahaan Asuransi di Indonesia yang terdapat pada Majalah Info Bank Tahun 2012) - Siregar, Budi Gautama (Institut Agama Islam Negeri Padangsidimpuan, 2014)
AbstractThis research is done to test variable Assets's (AS), Profit is Margin (PM), Solvency ratio (RS), Liquidity (LK) to financial Performance (KK) insurance company. Data that is utilized is secondary data which is insurance company finance data that published by Bank Info on year 2012. analisis's tech that is utilized is analisis double regression and menggnunakan's hypothesis quiz tests t partially, quiz f simultan's ala with of significance's level 5 % and determinant coefficient quiz. Analysis's result data that is done by using SPSS.20 was gotten to usufruct that Assets (AS), Profit is Margin (PM), Liquidity (LK) don't have influence that signifikan to financial Performance (KK) insurance company whereas Solvency Ratio (RS) having influence that signifikan to financial performance. While ability predicts of variable fourth that independent to financial performance as big as 50. 6 % , meanwhile its rest 49.4 % worded by variable is other variable that doesn't be worded deep model observational it.Kata Kunci : Assets, Profit Margin, Rasio Solvabilitas, Likuiditas dan Kinerja